Inhibitory Effect of Human Anti-CA I Autoantibodies and Development of Monoclonal Antibody mAb 2B8 Targeting Carbonic Anhydrase I - Petra Chalova; Barbora Jankovicova; Veronika Dvorakova; Eliska Zelinkova; Zuzana Bilkova; Marcela Slovakova; Lucie Korecka; Petr Muller; Maksym Danchenko; Lenka Minichova; Jan Lakota; Ludovit Skultety (Mediators of Inflammation)
Spontaneous tumor regression is a recognized phenomenon across various cancer types. Recent research emphasizes the alterations in autoantibodies against carbonic anhydrase I (CA I) (anti-CA I) levels as potential prognostic markers for various malignancies. Particularly, autoantibodies targeting CA I and II appear to induce cellular damage by inhibiting their respective protein’s catalytic functions. Our study illuminates the profound impact of anti-CA I autoantibodies from patient serum on the esterase activity of human CA I, exhibiting inhibitory effects akin to the acetazolamide inhibitor. Concurrently, our newly synthesized mouse monoclonal IgG antibody, mAb 2B8, against human CA I showcased a potent inhibitory action. An in-depth exploration into mAb 2B8′s binding dynamics with its target enzyme was undertaken. Leveraging epitope extraction and phage display library techniques, we identified the amino acid sequence DFWTYP (positions 191–196 of CA I) as crucial for mAb 2B8′s interaction. In 3-D structural analysis, this sequence is spatially adjacent to a previously identified epitope (DFWTYP) that interacts with patient-derived autoantibodies. Critically, mAb 2B8 demonstrated an ability to infiltrate eukaryotic cells, engaging specifically with its intracytoplasmic target. This positions mAb 2B8 as a promising model for future studies aimed at tumor cell eradication.